SOME PROBLEMS AND SOLUTIONS FOR THE FORMATION OF A NATIONAL INNOVATION SYSTEM (Multidisciplinary Journal of Science and Technology, 2024)
The article is about the directions of formation and development of the national innovation system of the Republic of Uzbekistan. The article investigates factors, problems and solutions affecting the formation and development of the national innovation system, and also develops a model of the national innovation system.